2009
DOI: 10.1373/clinchem.2009.125732
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric C-Reactive Protein Decreases Acetylated LDL Uptake in Human Endothelial Cells

Abstract: BACKGROUND: C-reactive protein (CRP) is a risk marker for cardiovascular disease and has been implicated in atherogenesis. In atherosclerotic plaques, it colocalizes with oxidized LDL (oxLDL) and promotes oxLDL uptake by macrophages, suggesting an important crosstalk between CRP and lipid processing. A growing body of evidence indicates the existence of distinct configurations of human CRP, native pentameric (nCRP) and structurally modified monomeric (mCRP), that elicit opposing bioactivities in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 17 publications
(16 reference statements)
0
28
0
Order By: Relevance
“…atherogenesis). Moreover, tissue-associated mCRP, irrespective of its redox state (15), may exert antiatherosclerotic actions, in particular at initial stages of plaque development, by promoting opsonic activation of the early complement pathway and non-inflammatory clearance of damaged cells (14,28,32,33) and by inhibiting foam cell formation (34,35). Overall, these would underlie the seemingly counterintuitive findings of the in vivo atheroprotective effects of Cys-mutated mCRP (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…atherogenesis). Moreover, tissue-associated mCRP, irrespective of its redox state (15), may exert antiatherosclerotic actions, in particular at initial stages of plaque development, by promoting opsonic activation of the early complement pathway and non-inflammatory clearance of damaged cells (14,28,32,33) and by inhibiting foam cell formation (34,35). Overall, these would underlie the seemingly counterintuitive findings of the in vivo atheroprotective effects of Cys-mutated mCRP (18).…”
Section: Discussionmentioning
confidence: 99%
“…Our results identify spatial localization as a novel determinant for the highly context-dependent actions of CRP isoforms within the vessels. Tissue-resident mCRP may pri- marily act as a pattern recognition molecule to facilitate noninflammatory complement activation (14,15,32) and macrophage clearance (34,35) within vessels undergoing chronic inflammation. However, in acute vascular inflammation, mCRP might be present in the circulation for an extended period of time as a consequence of endothelial damage, enhanced conversion, or transportation by microparticles (22) or activated platelets (11,13,23).…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that the induction and activation of LOX-1 in the smooth muscle might have occurred after a long-term exposure of coronary arterioles to abluminal CRP for 12 hours and contributed to the enhanced PAI-1 expression. It is worth noting that a conformational change of CRP from the native pentamer to a monomer form has been shown to alter its bioactivity and receptor binding 66,67 and thus may contribute to our disparate results in arterioles versus HCAEC. However, it has been shown that only native CRP binds to CD32 and LOX-1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dissociation of CRP into mCRP significantly enhances the ligand interaction capacity. Irrespective to its redox state, mCRP can regulate LDL metabolism [59,104] and opsonic activation of the complement pathway [60], likely exerting atheroprotective actions, in particular during the initial stages of atherogenesis [105] by promoting the clearance of the damaged material. Further reduction of the intra-subunit disulfide bond in mCRP unlocks the CBM, thereby unmasking pro-inflammatory activities, which may accelerate disease progression and trigger acute events.…”
Section: Discussionmentioning
confidence: 99%